THE EXPRESSION OF VEGF IN VAGINAL TISSUE OF MENOPAUSAL ANIMAL MODELS AFTER TREATED WITH ETHANOL EXTRACT OF PURPLE SWEET POTATO (IPOMEA BATATA L.) - Sugiritama, I Wayan; Wiryawan, I Gusti Nyoman Sri; Yoni Komalasari, Ni Luh Gede; Wahyuniari, Ida Ayu Ika; Dewi Ratnayanti, I Gusti Ayu (E-Jurnal Medika Udayana; Vol 14 No 6 (2025): E-Jurnal Medika Udayana, 2025)
Vaginal atrophy is a common complain in menopausal women as the sexual organ dysfunction. The features of vaginal atrophy including thinning of epithelium and decreasing in collagen fiber in the stroma therewith reduced blood vessels and vascularization by reason of decreased angiogenesis factors stimulation. Vascular endothelial growth factor (VEGF), a crucial mediator regulated by estrogen in angiogenesis, is involved in this process. Hormone Replacement Therapy (HRT) has proven effective in alleviating vaginal atrophy symptoms and enhancing vaginal wall vascularization, but it poses potential serious side effects. Phytoestrogens serve as a safer alternative to estrogen, demonstrating the ability to increase VEGF expression in the vaginas of ovariectomized mice and improve vaginal atrophy symptoms. Anthocyanins, a group of flavonoids with known phytoestrogenic activity both in vitro and in vivo, are found in high concentrations in purple sweet potato tubers. Several studies confirmed the phytoestrogenic activity of ethanol extracts from purple sweet potato tubers. Previous research indicates that these extracts increased epithelial thickness, epithelial maturation index, and the expression of estrogen receptors ? and ?, whilst maintaining vaginal pH. This pure experimental study followed a Post Test Only Control Group Design, aiming to investigate the effects of ethanol extract from purple sweet potato tubers on VEGF expression in the vaginal tissue of a menopausal animal model. Thirty-eight female Wistar rats, aged 16-18 weeks, subjected to bilateral ovariectomy, were divided into two groups: treatment group (P1) and control group (P0). After 30 days of treatment, the experimental animals were sacrificed, and vaginal tissues were collected for histological preparation and VEGF immunohistochemical staining. The research findings revealed that VEGF expression in the P1 group was 3.59±1.23, while in the P0 group, it was 0.8±0.57. Independent Sample T-test results indicated a significant difference (p<0.05) in VEGF expression between the two groups. In conclusion, the group treated with ethanol extract purple sweet potato tubers exhibited significantly higher VEGF expression in vaginal tissue compared to the control group